Chromosome analysis and sorting - Doležel, Jaroslav; Lucretti, Sergio; Molnár, István; Cápal, Petr; Giorgi, Debora (Cytometry. Part A, 2021)
Flow cytometric analysis and sorting of plant mitotic chromosomes has been mastered by only a few laboratories worldwide. Yet, it has been contributing significantly to progress in plant genetics, including the production of genome assemblies and the cloning of important genes. The dissection of complex genomes by flow sorting into the individual chromosomes that represent small parts of the genome reduces DNA sample complexity and streamlines projects relying on molecular and genomic techniques. Whereas flow cytometric analysis, that is, chromosome classification according to fluorescence and light scatter properties, is an integral part of any chromosome sorting project, it has rarely been used on its own due to lower resolution and sensitivity as compared to other cytogenetic methods. To perform chromosome analysis and sorting, commercially available electrostatic droplet sorters are suitable. However, in order to resolve and purify chromosomes of interest the instrument must offer high resolution of optical signals as well as stability during long runs. The challenge is thus not the instrumentation, but the adequate sample preparation. The sample must be a suspension of intact mitotic metaphase chromosomes and the protocol, which includes the induction of cell cycle synchrony, accumulation of dividing cells at metaphase, and release of undamaged chromosomes, is time consuming and laborious and needs to be performed very carefully. Moreover, in addition to fluorescent staining chromosomal DNA, the protocol may include specific labelling of DNA repeats to facilitate discrimination of particular chromosomes. This review introduces the applications of chromosome sorting in plants, and discusses in detail sample preparation, chromosome analysis and sorting to achieve the highest purity in flow‐sorted fractions, and their suitability for downstream applications. Flow cytometric analysis allows high throughput classification of mitotic chromosomes according to DNA amount and quantity of some DNA repeats. Flow sorting then simplifies genome sequencing and gene cloning by dissecting genomes into the individual chromosomes and greatly reducing DNA sample complexity. Purified chromosome fractions facilitate the analysis of three‐dimensional organization of DNA in condensed chromosomes and characterization of their proteome. This review introduces the applications of chromosome sorting in plants, and discusses in detail sample preparation, chromosome analysis and sorting to achieve the highest purity in flow‐sorted fractions, and their suitability for downstream applications.